2012
DOI: 10.1111/j.1349-7006.2012.02334.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of TAC‐101, an oral synthetic retinoid, in Japanese patients with advanced hepatocellular carcinoma

Abstract: Preclinical models have shown that TAC‐101 (4‐[3,5‐bis(trimethylsilyl) benzamide] benzoic acid), an oral synthetic retinoid, has antitumor activity in hepatocellular carcinoma (HCC). We conducted a phase I study in Japanese patients with advanced HCC to examine the pharmacokinetics, recommended dose, safety, and efficacy of TAC‐101. The administered dose of TAC‐101 was 10 mg/day in four patients (level 1), 20 mg/day in six (level 2), and 30 mg/day in three (level 3). There was no dose‐limiting toxicity at leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Two superiority trials compared sorafenib with radioembolization, SARAH and SIRveniB, in locally advanced HCC, and they were also reported at EASL2017 and ASCO 2017; however, these trials failed to meet their primary endpoints, with one criticism being the difficulty in performing clinical-trials of first-line HCC while using OS as the endpoint. A phase I study with TAC-101, an oral synthetic retinoid, with Japanese HCC patients showed positive anti-tumor activity with a satisfactory toxicity profile [57]. There is an ongoing phase III (NCT00756782) study that combines TAC-101 and transcathetar arterial chemoembolization (TACE) vs. TACE alone in Japanese HCC patients [58].…”
Section: Molecular Targeted Therapies For Hccmentioning
confidence: 99%
“…Two superiority trials compared sorafenib with radioembolization, SARAH and SIRveniB, in locally advanced HCC, and they were also reported at EASL2017 and ASCO 2017; however, these trials failed to meet their primary endpoints, with one criticism being the difficulty in performing clinical-trials of first-line HCC while using OS as the endpoint. A phase I study with TAC-101, an oral synthetic retinoid, with Japanese HCC patients showed positive anti-tumor activity with a satisfactory toxicity profile [57]. There is an ongoing phase III (NCT00756782) study that combines TAC-101 and transcathetar arterial chemoembolization (TACE) vs. TACE alone in Japanese HCC patients [58].…”
Section: Molecular Targeted Therapies For Hccmentioning
confidence: 99%
“…Treatment of osteosarcoma and chondrosarcoma cell lines with all-trans RA has shown reversible growth inhibition and simultaneously blocking of colony formation. , Retinoids have recently entered different phases of clinical trials for the treatment of solid tumors. , These molecules include TAC-101 (Taiho Pharmaceuticals, Japan, and tazarotene (Allergen, USA).…”
Section: Retinoid Receptors As Drug Targetsmentioning
confidence: 99%
“…260,261 Retinoids have recently entered different phases of clinical trials for the treatment of solid tumors. 262,263 These molecules include TAC-101 (Taiho Pharmaceuticals, Japan, and tazarotene (Allergen, USA).…”
Section: Cancer Therapeuticsmentioning
confidence: 99%
“…4-HPR has activity against tumours by generating reactive oxygen species [ 76 , 87 , 88 ], increasing dihydroceramide production [ 87 , 89 91 ] and natural killer cell activity [ 92 , 93 ] and inhibiting angiogenesis [ 89 , 94 ]. TAC-101 has shown efficacy in inhibiting liver tumour growth in particular of hepatocellular carcinoma [ 95 , 96 ]. Synthetic retinoids, approved from FDA for dermatological purposes, have a potential antitumour activity.…”
Section: Retinol and Derivativesmentioning
confidence: 99%